Chapter 18 From the implementation gap to Indigenous empowerment Prior consultation in Latin America - Wright, Claire (Taylor & Francis, 2019)
This conclusion presents some closing thoughts on the concepts covered in the preceding chapters of this book. The book deals with an important conceptual question: how useful is the "implementation gap" as an approach to understanding Indigenous rights? It describes the active participation of Indigenous organisations in multilateral negotiations over the creation of international documents - particularly the United Nations Declaration on the Rights of Indigenous Peoples - but their somewhat limited impact on the scope of participation, consultation, and consent in the texts finally adopted by States. The book shows that Environmental Impact Assessments - which should in theory help to protect Indigenous Peoples' interests - in fact account for many deficiencies in consultations over the extraction of natural resources in Bolivia, given that they fail to identify all impacts and reflect the government's pro-extraction bias.